Exploring time-telling expressions: A cross-linguistic study of German, Czech, and Russian - Panfilova, Elena; Mertins, Barbara (Linguistik Online, 2026)
This study explores how speakers of German, Czech, and Russian read analog clocks and which of the two distinct systems for expressing time (absolute or relative) they tend to prefer. Additionally, we investigated the reference point hypothesis in languages that have not previously been studied in this context. Our findings reveal that speakers of German, Czech, and Russian predominantly use relative expressions. Furthermore, our in-depth analyses of time expressions in Czech and Russian revealed a propensity to transition from the absolute to the relative system near the hourly reference point. Conversely, in German, more varied expressions were found around the half-hour region, where the reference point shifts from the past to the upcoming hour. These results provide new insights into the traditions of time-telling in a cross-linguistic comparison.